2020
DOI: 10.1097/olq.0000000000001194
|View full text |Cite
|
Sign up to set email alerts
|

“Sex in the Time of COVID”: Clinical Guidelines for Sexually Transmitted Disease Management in an Era of Social Distancing

Abstract: All New Yorkers should stay home as much as possible and minimize contact with others to reduce the spread of COVID-19. Sex is a normal part of life and should always be with the consent of all parties. This document offers strategies to reduce the risk of spreading COVID-19 during sex. Decisions about sex and sexuality need to be balanced with personal and public health. During this extended public health emergency, people will and should have sex. Consider using harm reduction strategies to reduce the risk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 11 publications
(8 reference statements)
0
38
1
Order By: Relevance
“…However, the authors are unaware of evidence to support such a change, and there is evidence to support the notion that sex and casual encounters were still occurring. 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…However, the authors are unaware of evidence to support such a change, and there is evidence to support the notion that sex and casual encounters were still occurring. 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, the HIV epidemic in the United States was experiencing modest downtrends due in part to successful harm reduction strategies, such as HIV pre-exposure prophylaxis (PrEP), as well as increasing testing to identify new cases, improving linkage to care, and more convenient and tolerable dosing of antiretroviral (ART) therapy [ 7 ]. Early COVID-19 mitigation strategies affected our ability to provide prompt, in-person care, leading to a tremendous shift to virtual medicine platforms, including telephone and video telemedicine [ 8 ]. This transition allowed care to continue for many, highlighting a new avenue for ongoing care [ 9 ].…”
Section: Covid-19 Impact On Hiv and Sexual Healthcarementioning
confidence: 99%
“…COVID-19 has disproportionately affected non-white, historically marginalized communities in the US, ranging from African Americans ( 40 ) to Native Americans ( 41 ). Moreover, the COVID-19 pandemic continues to threaten access to sexual health services, including follow-up care such as expedited partner tracing ( 42 , 43 ), and thus may further exacerbate existing racial/ethnic health disparities. A recent survey of sexual health providers indicated that only 18% of respondents could offer STI testing to asymptomatic patients, 80% were treating patients without diagnostic testing, and only 25% of respondents could maintain HIV testing ( 42 ).…”
Section: Unique Impact Of Covid-19mentioning
confidence: 99%
“…A recent survey of sexual health providers indicated that only 18% of respondents could offer STI testing to asymptomatic patients, 80% were treating patients without diagnostic testing, and only 25% of respondents could maintain HIV testing ( 42 ). Recommendations for providing STI clinical care during the COVID-19 pandemic include deferring asymptomatic patient screening visits, resorting to syndromic management using phone-based interviews, and treating with oral instead of intramuscular antibiotics ( 43 ).…”
Section: Unique Impact Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation